Streptococcus pneumoniae Serotypes Carried by Young Children and Their Association With Acute Otitis Media During the Period 2016–2019 - Ekinci, Esra; Desmet, Stefanie; Van Heirstraeten, Liesbet; Mertens, Colette; Wouters, Ine; Beutels, Philippe; Verhaegen, Jan; Malhotra-Kumar, Surbhi; Theeten, Heidi; , NPcarriage Group (Frontiers in Pediatrics, 2021)
Background:Streptococcus pneumoniae (Sp) is a major cause of acute otitis media (AOM). Pneumococcal conjugate vaccine (PCV) programs have altered pneumococcal serotype epidemiology in disease and carriage. In this study, we used samples collected during a cross-sectional study to examine if the clinical picture of acute otitis media (AOM) in young children exposed to the PCV program in Belgium was related to the carried pneumococcal strains, and if their carriage profile differed from healthy children attending daycare centers. Material/Methods: In three collection periods from February 2016 to May 2018, nasopharyngeal swabs and background characteristics were collected from children aged 6–30 months either presenting at their physician with AOM (AOM-group) or healthy and attending day care (DCC-group). Clinical signs of AOM episodes and treatment schedule were registered by the physicians. Sp was detected, quantified, and characterized using both conventional culture analysis and real-time PCR analysis. Results: Among 3,264 collected samples, overall pneumococcal carriage and density were found at similar rates in both AOM and DCC. As expected non-vaccine serotypes were most frequent: 23B (AOM: 12.3%; DCC: 17.4%), 11A (AOM: 7.5%; DCC: 7.4%) and 15B (AOM: 7.5%; DCC: 7.1%). Serotypes 3, 6C, 7B, 9N, 12F, 17F, and 29 were more often found in AOM than in DCC (p-value < 0.05), whereas 23A and 23B were less often present in AOM (p-value < 0.05). Antibiotic non-susceptibility of Sp strains was similar in both groups. No predictors of AOM severity were identified. Conclusion: In the present study, overall carriage prevalence and density of S. pneumoniae were found similar in young children with AOM and in healthy children attending day-care centers in Belgium. Certain serotypes not currently included in the PCV vaccines were found to be carried more often in children with AOM than in DCC, a finding that might suggest a relationship between these serotypes and AOM.